2001
DOI: 10.1177/004051750107100308
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dehydration on the Crystalline Structure and Strength of Developing Cotton Fibers

Abstract: Cotton fibers develop a significant crystalline structure during the first week of secondary wall synthesis. Marked increases in the degree of crystallinity, crystallite dimensions, and breaking forces occur between 20 and 30 days post-anthesis (dpa). As the fiber cells mature and dehydrate, the cylindrical tubes collapse into convoluted ribbons. The dried fibers have lower breaking strength and higher breaking elongation. Wide-angle x-ray diffraction and solid-state NMR results show lowered average crystallit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 28 publications
1
28
0
1
Order By: Relevance
“…The observed CI XRD readings from a small set of fibers at various growth periods were in good agreement with previously reported values for two cotton varieties at different developmental stages. 1,3 When making a comparison with cottons from commercial bales, the observed CI XRD values were between the reported CI range 73-80% (on Turkmenistan and Uzbekistan native cottons) 16 and those of either 53-69% (on Egyptian cottons) 17 or 57-64% (on Saudi Arabian cottons). 18 Hence, they concluded that using ATR-FTIR to assess the cotton fiber CI was appropriate and reasonable.…”
mentioning
confidence: 69%
“…The observed CI XRD readings from a small set of fibers at various growth periods were in good agreement with previously reported values for two cotton varieties at different developmental stages. 1,3 When making a comparison with cottons from commercial bales, the observed CI XRD values were between the reported CI range 73-80% (on Turkmenistan and Uzbekistan native cottons) 16 and those of either 53-69% (on Egyptian cottons) 17 or 57-64% (on Saudi Arabian cottons). 18 Hence, they concluded that using ATR-FTIR to assess the cotton fiber CI was appropriate and reasonable.…”
mentioning
confidence: 69%
“…Dehydration of natural fibers has been shown to decrease the crystallinity 5 and the order 6 of the crystalline domains in never-dried cotton. This loss can be controlled to some extent by slowly drying cotton at high temperatures, as demonstrated by Iyer et al, who were able to retain a higher degree of crystallinity of the fibers in the final dry state.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the low extractives content of balsa (1% by mass) in comparison to other woods (higher than 8% by mass) [10], [11], and the high crystallinity of its cellulose (around 90%) which can provide better mechanical properties, dimensional stability, chemical resistance, balsa can represent a great alternative raw material to produce cement-bonded particleboards [12].…”
mentioning
confidence: 99%